A hybrid sequential approach for solving environmentally constrained optimal scheduling in co-generation systems. (November 2021) - Goudarzi, Arman; Zhang, Chunwei; Fahad, Shah; Mahdi, Ali Jafer
Abstract: The ever-growing trend of electricity demand and environmental concerns have mandated the operation of electrical energy grids in a more economical and environmentally friendly manner. In the past few years, the integration of combined heat and power units has offered a promising solution to these concerns, however, at the same time a new challenging problem has revealed itself that is finding a simultaneous optimal solution between two competing criteria of power and heat. Furthermore, this problem will be more complex when the reduction of emission gasses is taken into consideration. Thus, to solve optimal scheduling of combined heat and power units, this study proposes an intelligent sequential algorithm based on the hybridization of teaching and learning-based optimization algorithm and an improved version of particle swarm optimization. The proposed algorithm is uniquely capable of the concurrent minimization of total generation costs and multi-pollutant gasses while several physical, operational, and environmental constraints are considered. Also, to ensure the safe maintenance of systems' constraints, this study employs an adaptive violation constraint handling technique in conjunction with the proposed hybridized optimization algorithm. Finally, the performance of the proposed algorithm is compared to the recently developed methods, in which the proposed algorithm of the study outperforms all the other algorithms and achieves up to 2.2% lower overall costs of operation in most of the studied cases. Highlights: A sequential metaheuristic algorithm based on hybridization of TLBO and IPSO is proposed. An adaptive penalization constraint handling technique is designed. A pragmatic method for solving CHPEED problem model is formulated. Several price penalty factors are developed to incorporate the cost of emission gasses in CHPEED problem.